Cell‐Penetrating and Neurotargeting Dendritic siRNA Nanostructures1. Issue 6 (17th December 2014) - Brunner, Korbinian; Harder, Johannes; Halbach, Tobias; Willibald, Julian; Spada, Fabio; Gnerlich, Felix; Sparrer, Konstantin; Beil, Andreas; Möckl, Leonhard; Bräuchle, Christoph; Conzelmann, Karl‐Klaus; Carell, Thomas
Abstract: We report the development of dendritic siRNA nanostructures that are able to penetrate even difficult to transfect cells such as neurons with the help of a special receptor ligand. The nanoparticles elicit strong siRNA responses, despite the dendritic structure. An siRNA dendrimer directed against the crucial rabies virus (RABV) nucleoprotein (N protein) and phosphoprotein (P protein) allowed the suppression of the virus titer in neurons below the detection limit. The cell‐penetrating siRNA dendrimers, which were assembled using click chemistry, open up new avenues toward finding novel molecules able to cure this deadly disease. Abstract : siRNA dendrimers with an anandamide receptor ligand are accessible through a click‐chemistry approach, and are taken up even by sensitive neural cells. Silencing of two key proteins of the rabies virus was achieved, allowing the suppression of the viral titer in infected neurons below the detection limit.